Emissions and built form – an analysis of six Canadian cities. Issue 2 (March 2015) - Rashidi, Taha Hossein; Kanaroglou, Pavlos; Toop, Erin; Maoh, Hanna; Liu, Xudong
Abstract : A direct result of population growth in large cities is an increased demand for public transit, goods movement, and road transportation. This increase in transportation demand consequently results in increases in mobile source emissions. Given the large amount of greenhouse gas (GHG) emissions produced by the Canadian resource industries, Canadian cities must rein in mobile source pollution if the country is to improve its status on the world stage. This study addresses this issue through presenting a Canada-specific framework for estimating mobile source emissions at the citywide level. Several air pollutants – including CO2, NO2, particulate matters (PM2·5 and PM10), and air toxics – are considered in this exercise, and summarized using a principal component analysis (PCA). Aggregate emissions are compared to various built form and travel behavior attributes for each respective city. The results indicate that population, travel to work behavior, and various built form attributes indeed impact transportation emissions at the citywide level.